Application of the Self Organized Learning Environments Model to Improve Critical Thinking Skills of Grade VI Elementary School Students - Oktafianti Kartika; Sapriya (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
This study was motivated by the low level of students' critical thinking skills in the learning process. This is based on the findings when researchers made observations, where during learning activities students were unable to provide a simple explanation of the material being studied, unable to conclude, unable to provide an explanation of the material being studied, and unable to identify assumptions. This is because applying a learning model is less able to develop students' critical thinking skills. This study aims to determine and get an overview of the improvement of critical thinking skills of grade VI elementary school students by applying the SOLE (self-organized learning environments) learning model. The method used in this research is Classroom Action Research (PTK) model Kemmis and Mc. Taggart model. This research was conducted in grade VI elementary school, as many as two cycles. Each cycle consists of one lesson and four stages, namely, planning, implementation, observation, and reflection. The instruments used in this research are observation sheets, field notes, test question sheets, and documentation. The results of this study showed an increase in the percentage of students' critical thinking skills in cycle I by 63% with a good category, in cycle II to 82% with a very good category. From these results it can be seen that there was an increase from cycle I to cycle II by 19%. This proves that the SOLE (Self Organized Learning Environments) learning model can improve the critical thinking skills of grade VI students in one of the elementary schools.